مقارنة فعالية وتحمّل كل من بنزوات البنزيل 25% والبرمترين 5% موضعياً في علاج الجرب لدى البالغين - بدور, رولا (Latakia University Journal -Medical Sciences Series, 2018)
ـشملت الدراسة 166 مريضاً مصاباً بالجرب من مراجعي العيادة الجلدية الخارجية في مشفى تشرين الجامعي في اللاذقية بين عامي 2014 ـ 2016. تم تقسيم المرضى إلى مجموعتين: ضمت الأولى 86 مريضاً عولجوا بمستحلب بنزوات البنزيل 25% وضمّت الثانية 80 مريضاً عولجوا بمستحلب البرمترين 25%. كانت نسب الشفاء متقاربة للدوائين في نهاية العلاج دون فارق هام إحصائياً (P-value=0.079 > 0.05) وكان تحمل البرمترين أفضل من تحمل بنزوزات البنزيل مع فارق هام إحصائياً (P-value = 0 < 0.05) This study included 166 scabietic Patients attending the outpatient clinic of the Tishreen university hospital at Lattakia from 2014 to 2016. Patients chosen were divided into two groups, the first included 86 Patients and was treated by topical Benzyl benzoate lotion 25%. the second included 80 Patients and was treated by topical Permethrin lotion 5%. The efficacy of both of the treatments was approximately the same with better tolerance to Benzyl benzoate than Permethrin with statistically significant correlation (P value<0.05)